Programas de orientação profissional: análise sobre seu desenvolvimento e aplicação a partir de pesquisas em análise do comportamento - Luppi, Adriana Mesquita Ribeiro (2014)
Behavioral programs for professional guidance provide conditions so that the person learns to emit the choice behavior of your profession from the analysis of variable and the consequences of each professional option to be chosen. The aim of the present research was analyze the behavioral programs of professional guidance, developed and applied by Behavior Analysts, to identify their characteristics and objectives, beside pointing the difficulties found and reached result. For this analysis development were selected six publications which presented and described the intervention programs in professional guidance and had been planned according to Behavior Analysis. The material of analysis used criteria supported in principle of Behavior Analysis: a) clear formulation of objectives to be achieved; b) prerequisite survey; c) evaluation of previous repertoire; d) procedure planning of target behavior installation; e) respect to the rhythm of participant learning; f) planning of maintenance procedure of target behavior and g) planning of generalization procedure of target behavior. Through the result was possible to identify that, despite all the programs have present the effectiveness related to increase of repertoire of behaviors related to choice, most of them did not strictly follow the principles of Behavioral Analysis which must be applied to the planning of a Behavioral Intervention Program. These principles provided a basic structure for a planning program to ensure that the installed behavior could be kept out of the therapeutic environment and possibly get permanently integrated to the individual`s behavioral repertoire. Thus, this effectiveness presented immediately after completion of procedures cannot assure the installed behaviors to be kept after the program completion. Nevertheless, we can`t fail to consider that the proposed programs took an important step to help the youngsters choosing their career, indicating that a behavioral intervention program, planned according to the Behavior Analysis, is a feasible proposal which needs to be improved